Pengubahan Organisasional Madrasah Sukses Berbasis Nilai-Nilai Religius Kepala Madrasah (Studi Kasus Pada Madrasah Ibtidaiyah Negeri I Malang) - Walid, Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The success of madrasah can simply reflect values and beliefs owned by the leader of madrasah on what to achieve by the school. Additionally, values and beliefs are potentially influential on leadership practice of madrasah leader for the advancement of madrasah, started from the leadership processes and procedures. For the research focus is centered on the â€œprocess of phenomenaâ€ of how religious values of madrasah leader can organize the change of madrasah to be successful and is aimed at obtaining deep comprehension on the phenomena, this research purposively employs qualitative approach. Besides, this research uses case study in which the religious values data of excellent madrasah leader in controlling the madrasah transformation comprise complex, holistic, natural and multi-interpreted events. There are three technniques to collect the data, known as participant observation, indepth interview and study documentation. The data are analyzed by testing, categorizing, tabulating, or recombining of empirical proofs to construct initial propositions of research. The concluding remarks of this research exemplify that values and beliefs that underpin madrasah leaderâ€™s belief to control revolution in Islamic Elementari School (MIN) I Malang is strongly believed by madrasah leader in which the school processes are its articulation form. The religious beliefs and values of MIN 1 Malang leader are optimism, confidence, sincerity and tawakkal (trust in God) that are combined by four traits of prophet Muhammad, namely siddiq (honesty), tabligh (openly human relations), amanah (trustworthiness) and fathanah (intelligence).